Child Martyrs in the Pantheon of Totalitarian Cultures (H. Steinhoff’s Film Hitlerjunge Quex) - Aleksandra V. Eliseeva (Studia Litterarum)
The article focuses on the film script for Hitlerjunge Quex (1933, director Hans Steinhoff) written by B.E. Luthge and K.A. Schenzinger. This film is an example of the national socialist propaganda cinematograph at work. The case study discusses the strategies of the child figure instrumentalization for ideological purposes. It draws parallels between the Nazi art and the Soviet art, cinema in particular where similar propaganda models are present, such as the cult of heroic pioneers. The narrative about the heroic deed and martyrdom of the young Nazi has much in common the story about Pavlik Morozov, popular in the Soviet time. The paper deals with ideologemes that unite the “child heroes” constructs in both totalitarian cultures: the myth about the impartiality and “innocence” of the child’s worldview, acclaimed superiority of the public welfare over family relations and others. It also studies the sources of such ideologemes, their connection with Christian, Enlightenment and other belief systems.